2016
DOI: 10.1155/2016/8738760
|View full text |Cite
|
Sign up to set email alerts
|

Naringenin Ameliorated Kidney Injury through Let-7a/TGFBR1 Signaling in Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is one of the most common complications of diabetes mellitus (DM). However, the exact mechanism is not clearly understood. In this study, our results showed that 24 h urinary protein, kidney index, and glomerular area were decreased, while creatinine clearance ratio was increased in DN rats when the rats were treated with NAR 50 mg/d for 6 weeks. Mesangial cell (MMCs) proliferation was inhibited in the NAR group by 3,(4,5-dimethyl-2-thiazolyl)-2,5-diphenyl-2H-tetrazolium bromide (MTT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 38 publications
0
34
0
Order By: Relevance
“…miR-199a has also been reported to be involved in inflammation via modulating the activation of NF-κB by targeting Klotho in lupus nephritis [42]. Sun et al reported the increased level of serum miR-199b-5p in diabetic patients [43]. They also indicated that the inhibition of miR-199b ameliorated TGF-β1-induced EMT and renal fibrosis via targeting SIRT1 in diabetic nephropathy [43].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-199a has also been reported to be involved in inflammation via modulating the activation of NF-κB by targeting Klotho in lupus nephritis [42]. Sun et al reported the increased level of serum miR-199b-5p in diabetic patients [43]. They also indicated that the inhibition of miR-199b ameliorated TGF-β1-induced EMT and renal fibrosis via targeting SIRT1 in diabetic nephropathy [43].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
“…Sun et al reported the increased level of serum miR-199b-5p in diabetic patients [43]. They also indicated that the inhibition of miR-199b ameliorated TGF-β1-induced EMT and renal fibrosis via targeting SIRT1 in diabetic nephropathy [43]. Kang et al suggested that miR-199b-5p targets klotho, thereby promoting renal tubular injury in diabetic nephropathy [77].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 99%
“…Dysregulated angiogenesis is considered to be one of the fundamental mechanisms regulating initiation and development of many diseases, such as cancer, heart disease and inflammation . In this study we found that TGFBR3 is a novel target of let‐7a.…”
Section: Discussionmentioning
confidence: 58%
“…It has been recently shown that let‐7a, along with other miRNAs may favour the “Off” switch of tumour angiogenesis in a mouse model of breast tumour undergoing hormone therapy . Intriguingly, TGFBR1, a member of TGFβ family, identified as potential target of let‐7, was critical for endothelium inflammation and cell differentiation …”
Section: Introductionmentioning
confidence: 99%
“…However, the role and mechanism of lincRNA ANRIL in HG-induced HMC apoptosis and Rg treatment are still unknown to the best of the authors' knowledge. let-7a was downregulated in both rats with DN and mesangial cells in an HG condition, and could negatively regulate the expression of TGFβ receptor 1 (18). Katayama et al (19) reported that glucose could significantly regulate the expression of let-7a by affecting promoter activity.…”
Section: Discussionmentioning
confidence: 96%